2010
DOI: 10.1063/1.3533021
|View full text |Cite
|
Sign up to set email alerts
|

A graphene quantum dot with a single electron transistor as an integrated charge sensor

Abstract: ABSTRACT:We have developed an etching process to fabricate a quantum dot and a nearby single electron transistor as a charge detector in a single layer graphene. The high charge sensitivity of the detector is used to probe Coulomb diamonds as well as excited spectrum in the dot, even in the regime where the current through the quantum dot is too small to be measured by conventional transport means.The graphene based quantum dot and integrated charge sensor serve as an essential building block to form a solid-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
91
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 29 publications
(21 reference statements)
1
91
0
Order By: Relevance
“…However, it is difficult to control and identify the energy structure of graphene QDs by traditional transport methods such as PAT, possibly because of edge states and puddles [33][34][35]. The sensitive microwave-based metrology used here allows us to study the dephasing rates in graphene DQDs, and whether they depend on the charge number in a DQD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to control and identify the energy structure of graphene QDs by traditional transport methods such as PAT, possibly because of edge states and puddles [33][34][35]. The sensitive microwave-based metrology used here allows us to study the dephasing rates in graphene DQDs, and whether they depend on the charge number in a DQD.…”
mentioning
confidence: 99%
“…Because the dephasing rate in grapheme DQDs has not been obtained by any other means namely photon-assisted tunneling (PAT), a traditional method, we now speculate here a possible reason. Using traditional methods involving charge transport, determining γ 2 is easily masked by the puddle and edge states [33][34][35] in an etched graphene structure. However, the resonant cavity here is mostly sensitive to the electrical dipole of the DQD and is affected much less by electrostatic disorder in the etched grapheme structure.…”
mentioning
confidence: 99%
“…Instead, the most viable way to confine charge carriers in graphene nowadays is based on etching nanostructures into graphene flakes [15]. So far, Coulomb blockade [16][17][18][19], excited states [20][21][22], charge sensing [23,24], and spin-filling sequences [25] have been studied in detail in etched graphene quantum dot devices. More recently, also charge pumps [26] and charge relaxation times of excited states [27] in graphene quantum dots have been investigated experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…This can be overcome by nanostructuring graphene, where it has been shown that an etching-based "paper cutting" technique leads to graphene nanodevices where transport is dominated by a disorder-induced energy gap. Consequently, graphene nanoribbons [4][5][6][7][8][9][10][11][12], single-electron transistors (SETs) [13][14][15], graphene quantum dots (QD) [16][17][18] even with charge detectors [16,19,20] and graphene double quantum dots [21][22][23][24][25] have been demonstrated successfully. These devices allowed the experimental observation of excited states [22,26], spin states [27] and the very few carrier regime [28].…”
Section: Introductionmentioning
confidence: 99%